Onicomicoses e tinea pedis em atletas do Planalto Médio do Rio Grande do Sul – Brasil - Sabadin, Clarice Elvira Saggin [UNIFESP] (2009)
Introduction: onychomycosis and tinea pedis are superficial fungal infections caused primarily by dermatophytes, which may interfere with personal performance, professional and social life. However, there are few investigations about mycoses situation among athletes. Objective: to investigate the prevalence of foot fungal infections, comparing athletes and non-athletes from the Middle Plateau of Rio Grande do Sul state, Brazil. Methods: one hundred male athletes, between 18 and 40 years, from the cities of Passo Fundo, Erechim, Tapejara and Sarandi were included in this study. The control group was consisted of 100 non-athletes at the same age and sex. Scales of the skin and/or nails were collected for direct examination and fungal culture. The chi-square and Mann-Whitney tests were employed with significance level of 0.05. Results: the prevalence of foot fungal infections was similar between athlete and non-athlete population. Among the athletes, we observed 32 positive cases for fungal infection: 16 of onychomycosis, 12 of tinea pedis and four of onychomycosis and tinea pedis association. Among non-athletes, there were 20 cases of fungal infection: 10 of onychomycosis, seven of tinea pedis and three of onychomycosis and tinea pedi association. The nails of the first and second toes were the most affected. Distal and lateral subungual onychomycosis was the main type of onychomycosis in both groups: athlete (90%) and non-athlete (100%). The identified dermatophytes (n = 39) were Trichophyton rubrum (56.5% and 56.3%), Trichophyton mentagrophytes (30.4% and 31.3%), Microsporum canis (8.7% and 6.2%), Epidermophyton floccosum (4.4% and 6.2%), respectively from athletes and non-athletes. Among the yeasts (n = 5), Candida albicans (40%), Candida parapsilosis (20%), Candida tropicalis (20%) and Trichosporon spp (20%) were identified among athletes. Among non-athletes (n = 2): C. albicans (50%) and C. parapsilosis (50%). Among the analyzed predisposing factors for onychomycosis in athletes, significance was found in: familial cases of fungal infection (p = 0.001), domestic animals contact (p = 0.007) and nail trauma (p = 0.033). In non-athletes, the habit of not using slippers in common use bathrooms and changing rooms (p = 0.014) and nail trauma (p = 0.004) were significant. Analyzing the same predisposing factors for tinea pedis, the habit of not using sandals in common use bathrooms and changing rooms (p = 0.001) was a predisposing factor for both groups and excessive sweating only in the group of non-athletes (p = 0.019). Conclusion: based on the results of this work, we concluded that there was no significant difference in foot fungal infections between the athlete and non-athlete groups, the main found agents were dermatophytes followed by yeasts.